2012
DOI: 10.1136/emermed-2012-201106
|View full text |Cite
|
Sign up to set email alerts
|

‘Do you know where your cyanide kit is?’: a study of perceived and actual antidote availability to emergency departments in the South West of England

Abstract: Stocking of important antidotes should be rationalised and simplified using central locations, preferably close to the ED. Clinically important antidotes may not be available for patients when they need them. Clear guidance should be available for staff detailing the location of antidotes. There is a need for clarification around the treatment of cyanide poisoning to facilitate rational antidote stocking for this potentially lethal condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Antidotes are an important tool in the management of poisoned patients, with timely administration being potentially lifesaving 1 2. Problems with availability of antidotes at the point of care have been reported worldwide with the potential for deleterious effects on patient outcomes 3–10. Guidance on antidote stocking is published in North America and the UK, and these emphasise the importance of timely availability 11–13.…”
Section: Introductionmentioning
confidence: 99%
“…Antidotes are an important tool in the management of poisoned patients, with timely administration being potentially lifesaving 1 2. Problems with availability of antidotes at the point of care have been reported worldwide with the potential for deleterious effects on patient outcomes 3–10. Guidance on antidote stocking is published in North America and the UK, and these emphasise the importance of timely availability 11–13.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several studies have reported that hospital pharmacies have inadequate stocks of antidotes available. [2][3][4][5][6] Administration and dosing errors have also been reported in the literature. 7,8 With new dosing strategies being introduced, use in special populations, expanded indications for established antidotes, and the reassessment and expansion of off-label indications for other medications, knowledge of antidotes remains paramount.…”
mentioning
confidence: 99%